'We're not very good at soccer': gender, space and competence in a Victorian primary school. Issue 2 (4th March 2019) - Spark, Ceridwen; Porter, Libby; de Kleyn, Lisa
ABSTRACT: This paper draws on findings from a pilot project conducted at an inner city primary school in Melbourne, Australia. Inviting grade six girls and boys (aged eleven and twelve) to focus on spaces of their schoolground, we learned about the ways in which gender, age, ethnicity, language ability and sporting competence influenced active play and belonging. Informed by the understanding that schoolgrounds, gender and active play are socially constructed, and children are active agents in these constructions, the paper examines how girls and boys consider and negotiate spatial politics. The methods of participant-led photography, focus groups and thematic analysis, reveal how children understand gendered spatialities. A strong story emerged of girls' experience of exclusion from active play spaces in particular, providing a perspective on the spatial and social performance of gender. The findings highlight the value of integrating a spatial analysis of schoolgrounds – and the gendered dynamics therein – for health, education and equity programmes.